2022
DOI: 10.3389/fonc.2022.930868
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of transarterial chemoembolization monotherapy or combination conversion therapy in unresectable hepatocellular carcinoma: A systematic review and meta-analysis

Abstract: BackgroundHepatocellular carcinoma (HCC) is a highly malignant disease with poor prognosis, and most cases were already considered unresectable at the time of presentation. Conversion therapy, as an emerging treatment, is designed to provide patients with initially unresectable hepatocellular carcinoma (uHCC) the opportunity to undergo radical resection. At present, conversion therapy for patients with uHCC remains controversial. Transarterial chemoembolization (TACE) is currently the most widely selected trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
(109 reference statements)
0
16
0
Order By: Relevance
“…Consequently, systemic damage caused by radiation was limited and minimized. [31] Advanced HCC patients with MVI exhibited poor tumor biological behavior, a high risk of postoperative recurrence, and a low long-term survival rate. [32] Several studies have explored different treatment strategies for this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, systemic damage caused by radiation was limited and minimized. [31] Advanced HCC patients with MVI exhibited poor tumor biological behavior, a high risk of postoperative recurrence, and a low long-term survival rate. [32] Several studies have explored different treatment strategies for this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Zhan et al have provided evidence that the combined therapy of radioembolization and immunotherapy is significantly effective and safe in treating HCC patients [107]. A study conducted by Li et al showed that the combination of TACE and hepatic arterial infusion chemotherapy (HAIC) has a more advantageous progression-free survival (PFS) due to its significantly higher conversion rate compared to conventional TACE (48% vs. 9%, respectively) [108]. Additionally, the administration of trans-arterial chemoembolization (TACE) followed by sorafenib treatment is found to be therapeutically effective in treating advanced HCC.…”
Section: Chemoembolization In Combination With Immunotherapy or Molec...mentioning
confidence: 99%
“…The use of TACE, TKIs, and ICIs has been found to increase residual liver volume in patients with intermediate to advanced HCC, thereby enhancing the safety of conversion resection (76). A meta-analysis of 18 studies found that the conversion rate of triple therapy (TACE+TKIs+ICIs) was 42%, which was higher than that of TACE alone (10%) and TACE combined with other therapies (19%) (77). The tumor response to triple therapy was superior to that of TACE alone or dual therapy (77).…”
Section: Combined Locoregional and Systemic Therapymentioning
confidence: 99%